2021
DOI: 10.1111/phn.12958
|View full text |Cite
|
Sign up to set email alerts
|

Global impact of physical inactivity and implications for public health nursing

Abstract: Physicalinactivity has been a public health problem worldwide for more than a decade. Of those who are physically active, a substantial percentage engage solely in low or very low physical activity (PA) levels. In the last 3 decades, the prevalence of PA in the United States has decreased with approximately 80% of adults not meeting the recommended guidelines for aerobic and muscle strengthening PA. The PA levels of youth have dramatically decreased with 85% of adolescents reporting no PA. Regular PA participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Lack of physical activity (PA) is considered a major public health problem in the 21st century [ 1 , 2 ]. Moreover, most of the young population is not physically active; that is, 81% of children and adolescents do not have sufficient levels of PA [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of physical activity (PA) is considered a major public health problem in the 21st century [ 1 , 2 ]. Moreover, most of the young population is not physically active; that is, 81% of children and adolescents do not have sufficient levels of PA [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant result of these interventions was the reduction in sitting time, especially during the total lockdown, with a mean of 30.1 hours per week. It is well known that sedentarism impacts the human body Page 13/17 [21] reducing muscular mass and cardiovascular tness and impairing metabolism and the endocrine and nervous systems. [22]Moreover, it has been demonstrated that muscle wasting occurs rapidly and is detectable within two days of inactivity, a key aspect that was considered in the application of the online interventions [16].…”
Section: Discussionmentioning
confidence: 99%
“…42 Insufficient physical activity is a contributing factor in the leading causes of death in the US 35 and a public health concern. 43,44 Physical inactivity (not meeting US national physical activity guidelines) has been linked to more severe COVID-19 infection outcomes. Patients with COVID-19 who were consistently inactive during the 2 years preceding the pandemic were 73% more likely to require intensive care and 2.5-times more likely to die of the infection than were patients who had consistently met physical activity guidelines.…”
Section: Extreme Heat Conditions Threaten Health Benefits Of Physical...mentioning
confidence: 99%